Chronic Inflammation and Insulin Resistance as Links between Metabolic Syndrome and Musculoskeletal Disorders - Deka, Emilia; Banatkiewicz, Joanna; Bartkowska, Oliwia; Czarnecka, Sofia; Bojanowska, Hanna; Babik, Karolina; Łuczyńska, Gabriela Ewa; Domińczak, Jan; Dobosz, Adam; Wojnowski, Antoni (Journal of Education, Health and Sport, 2026)
Background: Metabolic syndrome (MetS) affects approximately 25-30% of adults worldwide and is traditionally associated with cardiovascular complications. However, emerging evidence suggests that MetS may also substantially increase the risk of musculoskeletal disorders, including osteoarthritis, sarcopenia, and osteoporosis. Objectives: This review synthesizes current evidence on the molecular and pathophysiological mechanisms connecting MetS to musculoskeletal disorders, with particular focus on chronic inflammation and insulin resistance as central mediators. Methods: A comprehensive literature search was conducted across PubMed and Google Scholar, focusing on publications from 2018-2026. Search terms included metabolic syndrome, chronic inflammation, insulin resistance, musculoskeletal disorders, adipokines, osteoarthritis, and sarcopenia. After reviewing and ranking for relevance, 40 high-impact studies were selected to form the evidence base for this review [40]. Results: The literature reveals that chronic inflammation in MetS, characterized by elevated pro-inflammatory cytokines (IL-6, TNF-α, IL-1β) and dysregulated adipokines (leptin, adiponectin, resistin), creates a systemic inflammatory environment that directly impacts musculoskeletal tissues. Conclusions: Chronic inflammation and insulin resistance represent critical mechanistic links between MetS and musculoskeletal disorders. Interventions targeting inflammation and insulin sensitivity—including lifestyle modifications, omega-3 fatty acids, metabolic drugs (metformin, GLP-1 agonists), intermittent fasting, and inflammasome-targeting approaches—may offer benefits for both metabolic and musculoskeletal health.